2003
DOI: 10.1291/hypres.26.965
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiation on Fatty Liver and Metabolic Coronary Risk Factors among Atomic Bomb Survivors in Nagasaki

Abstract: In order to clarify the basic mechanism(s) linking radiation exposure and coronary heart disease (CHD), we here collected ultrasonographic data on fatty liver and measured levels of metabolic CHD risk factors from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 44 publications
2
31
1
Order By: Relevance
“…It has also been reported that peripheral T cells in obese individuals are somewhat activated, displaying increased expression levels of surface CD25 (a subunit of the IL2 receptor) and polarization towards a pro-inflammatory type-1 (T H 1) phenotype (10)(11)(12). It should be noted here that metabolic abnormalities, including serum levels of high triglyceride, low HDL cholesterol and fatty liver development, have been reported in association with radiation dose among A-bomb survivors (13)(14)(15). Moreover, emerging evidence from mouse studies suggests direct interactions between diet-induced obesity and biological responses to radiation, e.g., DNA double-strand breaks, microRNA expression and cell survival (16,17).…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…It has also been reported that peripheral T cells in obese individuals are somewhat activated, displaying increased expression levels of surface CD25 (a subunit of the IL2 receptor) and polarization towards a pro-inflammatory type-1 (T H 1) phenotype (10)(11)(12). It should be noted here that metabolic abnormalities, including serum levels of high triglyceride, low HDL cholesterol and fatty liver development, have been reported in association with radiation dose among A-bomb survivors (13)(14)(15). Moreover, emerging evidence from mouse studies suggests direct interactions between diet-induced obesity and biological responses to radiation, e.g., DNA double-strand breaks, microRNA expression and cell survival (16,17).…”
Section: Introductionmentioning
confidence: 51%
“…Low HDL cholesterol and fatty liver development have been reported to be associated with radiation dose among Abomb survivors (14). Although causal relationships cannot be determined from the cross-sectional analyses of the current study, it can be hypothesized that the maintenance of peripheral lymphocyte populations may have been affected by an unidentified pathway that could involve radiation-associated alterations in metabolic profiles, in particular altered lipid metabolism.…”
Section: Discussionmentioning
confidence: 75%
“…Akahoshi's group reported that radiation dose was positively associated with fatty liver (Akahoshi et al 2003). Wong's group reported the mean increase in serum cholesterol levels for the irradiated groups was significantly higher than that for non-irradiated groups (Wong et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of degenerative disease caused by radiation exposure has been reported (Wong et al 1999, White and Averner 2001, Akahoshi et al 2003, the degenerative changes in lipid metabolism after exposure to ionising radiation are poorly understood. Exposure to ionising radiation, e.g., g-rays, is one of the methods currently used to stress specific biological model system.…”
Section: Introductionmentioning
confidence: 99%
“…12,30 Obesity (from excess nutrition intake) leads to visceral fat accumulation. Visceral fat has high metabolic activity and releases free fatty acids and adipokines such as leptin, tumor necrosis factor-a, and adiponectin.…”
Section: Discussionmentioning
confidence: 99%